Kajian kepuasan pelancong terhadap kualiti perkhidmatan muzium Sabah - Douni, Rut (2007)
This study focus on the evaluation of tourists’ level of satisfaction towards Sabah Museum service quality. The traditional roles of museum had changed: as museum is no longer a place to keeps and exhibits the artifacts but now museum is one of the tourist destinations. Therefore, this study emphasize that tourist is the important aspect to consider in any activities organize by Sabah Museum so that service quality shall be enhanced. There are 158 respondents were selected randomly to get their respond on the service quality provided by Sabah Museum.